A Randomized Pharmacokinetic and Pharmacodynamic Evaluation of Every 8‐Hour and 12‐Hour Dosing Strategies of Vancomycin and Cefepime in Neurocritically ill Patients. Issue 9 (20th July 2018) - Kassel, Lynn E.; Van Matre, Edward T.; Foster, Charles J.; Fish, Douglas N.; Mueller, Scott W.; Sherman, Deb S.; Wempe, Michael F.; MacLaren, Robert; Neumann, Robert T.; Kiser, Tyree H.
Abstract : Purpose: Neurocritically ill patients have clinically significant alterations in pharmacokinetic parameters of renally eliminated medications that may result in subtherapeutic plasma and cerebrospinal fluid antibiotic concentrations. Methods: We conducted a prospective randomized open‐label study of adult neurocritically ill patients treated with vancomycin and cefepime. Vancomycin 15 mg/kg and cefepime 2 g were dosed at every‐8‐ or 12‐hour intervals. The primary outcomes were the achievement of pharmacodynamic (PD) targets related to time of unbound drug above minimum inhibitory concentrations (MIC) for 60% or more of the dosing interval ( f T > MIC ≥ 60%) for β‐lactams and ratio of 24‐hour area under the curve (AUC):MIC of 400 or greater for vancomycin. Results: Twenty patients were included in the study. They were divided equally between the every‐12‐hour and every‐8‐hour dosing groups. Patients (mean age 51.8 ± 11 yrs) were primarily male (60%) and white (95%), and most had an admission diagnosis of intracranial hemorrhage (80%). Compared with the every‐12‐hour group, the every‐8‐hour vancomycin group achieved target trough concentrations (higher than 15 μg/ml) significantly more frequently at initial measurement (0% vs 80%, p<0.01) and at 7–10 days (0% vs 90%, p=0.045) and achieved PD targets more frequently at increasing MICs. Similarly, compared with every‐12‐hour dosing, the every‐8‐hour cefepime dosing strategy significantly increased PD target attainment ( f T > MIC ≥ 60%) at an MIC of 8 μg/ml (20% vs 70%, p=0.02). Conclusions: This study demonstrated that more frequent dosing of vancomycin and cefepime is required to achieve optimal PD targets in adult neurocritically ill patients. The need for increased total daily doses is potentially secondary to the development of augmented renal clearance.